2011
DOI: 10.1007/s00203-011-0728-3
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum RNase E/G-type endoribonuclease encoded by NCgl2281 is involved in the 5′ maturation of 5S rRNA

Abstract: Corynebacterium glutamicum has one RNase E/G ortholog and one RNase J ortholog but no RNase Y. We previously reported that the C. glutamicum NCgl2281 gene encoding the RNase E/G ortholog complemented the rng::cat mutation in Escherichia coli but not the rne-1 mutation. In this study, we constructed an NCgl2281 knockout mutant and found that the mutant cells accumulated 5S rRNA precursor molecules. The processing of 16S and 23S rRNA, tRNA, and tmRNA was normal. Primer extension analysis revealed that the RNase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…A previous study suggested that C. glutamicum RNase E/G was more closely related to E. coli RNase G than to RNase E (36). We then showed that RNase E/G is involved in the processing of 5S rRNA, although it is not essential for cell viability (37). Here we show that RNase E/G is a novel posttranscriptional regulator of the glyoxylate cycle in C. glutamicum.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…A previous study suggested that C. glutamicum RNase E/G was more closely related to E. coli RNase G than to RNase E (36). We then showed that RNase E/G is involved in the processing of 5S rRNA, although it is not essential for cell viability (37). Here we show that RNase E/G is a novel posttranscriptional regulator of the glyoxylate cycle in C. glutamicum.…”
mentioning
confidence: 69%
“…Total cellular RNA from C. glutamicum ATCC 31831 and D2281 was isolated as described previously (37). Briefly, overnight cultures grown on CGC minimal medium containing 1% glucose at 30°C were washed and then inoculated into fresh CGC minimal medium containing 1% sodium acetate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A suicide vector, pCRA725, carrying the sacB gene was used for markerless gene deletion and gene modification (33). Using plasmids LKSΔrnZ, LKSΔybeY, and LKSΔrnR and C. glutamicum strain R as a wild type, ΔrnZ, ΔybeY, and ΔrnR strains were constructed by two-step homologous recombination, as described previously (34). The DNA fragment encoding the ffh gene fused with a FLAG tag (DYKDDDK) was cloned into plasmid pCRA725 (33), yielding LKSffh-FLAG.…”
Section: Fĭ-flagmentioning
confidence: 99%
“…Northern hybridization was performed as described previously (34). A digoxigenin (DIG)-labeled antisense RNA probe targeting the 4.5S RNA coding region (entire 4.5S RNA probe) and the 3= spacer region (3= spacer region-specific RNA probe) was produced according to the manufacturer's instructions (Roche).…”
Section: Fĭ-flagmentioning
confidence: 99%